High Correlation of the Response of Upper and Lower Lobe Small Airway Epithelium to Smoking - Harvey, Ben-Gary (Public Library of Science, 2013)
The distribution of lung disease induced by inhaled cigarette smoke is complex, depending on many factors. With the knowledge that the small airway epithelium (SAE) is the earliest site of smoking-induced lung disease, and that the SAE gene expression is likely sensitive to inhaled cigarette smoke, we compared upper vs. lower lobe gene expression in the SAE within the same cigarette smokers to determine if the gene expression patterns were similar or different. Active smokers (n = 11) with early evidence of smoking-induced lung disease (normal spirometry but low diffusing capacity) underwent bronchoscopy and brushing of the upper and lower lobe SAE in order to compare upper vs lower lobe genome-wide and smoking-responsive gene expression by microarray. Cluster and principal component analysis demonstrated that, for each individual, the expression of the known SAE smoking-responsive genes were highly correlated in upper and lower lobe pairs, although, as expected, there were differences in the smoking-induced changes in gene expression from individual to individual. These observations support the concept that the heterogeneity observed among smokers in the anatomic distribution of smoking-induced disease are not secondary to the topographic differences in the effects of cigarette smoke on the airway epithelium.